PURWARUPA ROBOT LENGAN PEMILAH OBJEK BERDASARKAN LABEL TULISAN SECARA REALTIME A PROTOTYPE OF REALTIME OBJECT CLASSIFIER ARM ROBOT BASED ON TEXT LABEL - , BRYAN NOVEGA WHILDAN BIMANTAKA; , Dr. Agus Harjoko ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The developments of technology not only in industrialized world, but also the world of education. One example is International Robot Contest (IRC) on humanoid category on object classifying mission.The main part of humanoid robot are both the webcam to identify the objects, and the arm of the robot itself to retrieve the object. In this study, has been made an arm robot which has 4 DOF, 1 gripper, and a webcam as the sensor. The arm robot will find the object whether ball, can, or cube within reach, take the object and put it on its label which has been located. For object identification process, the digital image processing is done by a computer using OpenCV library. Once the object is identified, then the robot will find the center point coordinates of the object, as a reference for arm robot to move servo motors by applying geometry inverse kinematics method. While the text label identification is done by using Tesseract library to process the image captured by webcam. The tests of the prototype in this study are done by testing the influence of light intensity during object identification, object retrieval and object placement accuracy testing. The light intensity testing shown the best result at 1,59 cd â 15,92 cd for the ball, 3,18 cd â 3,98 cd with threshold 50 â 200 for the can, and 2,39 cd â 3,98 cd with the threshold 50 - 200 for the cube. The object retrieval accuracy is 86,67%, and the object placement accuracy is 100%.